Enhancing Student Engagement and Learning Outcomes in TLE 9 Cookery Through the Use of Moodle as an Adaptive Learning Tool - Quimco, Keichie R.; Calvo, Sonny Rey M.; Manulat, Ma. Adele Fe M. (IIUM Journal of Educational Studies, 2025)
This study examines the effectiveness of the Moodle platform as an adaptive learning tool in enhancing student engagement, learning outcomes, and attitudes toward technology among Grade 9 Technology and Livelihood Education (TLE) Cookery students at B. Durano Integrated School in Danao City, Cebu, Philippines. Sixty Grade 9 students enrolled in TLE Cookery were randomly selected and assigned to either the experimental group (n=30), which received Moodle-based instruction, or the control group (n=30), which experienced traditional teaching methods. Academic achievement was measured using teacher-made pre-test and post-test assessments, while student perceptions of Moodle were evaluated via a validated questionnaire based on the Technology Acceptance Model (TAM), which assessed perceived usefulness, ease of use, computer self-efficacy, attitude, and intention to use. Quantitative data were analysed using independent samples t-tests to determine differences in learning gains, and descriptive statistics summarized TAM-related responses. Results indicated that students in the Moodle group achieved significantly greater improvement in post-test scores compared to the control group (p < 0.05). Additionally, Moodle users reported strong positive perceptions and high acceptance of the platform across all TAM dimensions. These findings highlight the value of incorporating adaptive digital platforms like Moodle in skill based education, providing evidence that such tools can promote academic success, engagement, and positive attitudes even in resource-limited environments.